Ensaios sobre Trabalho Infantil - Mesquita, Shirley Pereira de (2015)
This dissertation encompasses three chapters that study Child Labor. Below are the individual abstracts for each chapter. Chapter 1: Child labor and the wealth paradox: the role of Altruistic Parents Using data from Pakistan and quantile regression techniques, we study the effect of family wealth on the utilization of child labor. We find evidence of a positive relationship between land wealth and child labor only for children in the upper quantiles of the distribution. We hypothesize that the so-called "Wealth Paradox" in child labor documented elsewhere in the literature is driven by parental preferences. Chapter 2: Child labor and household wealth: an analysis for rural Brazil This chapter studies the effect of family wealth on the utilization of child labor in rural areas of Brazil. We using data from PNAD 2012 and the Censored Quantile Instrumental Variable (CQIV) which captures heterogeneity across the distribution of hours worked, and it deals with the problems of censorship and endogeneity in the data. We find evidences of a negative relationship between land wealth and child labor only for children in the lower quantiles of the distribution. On the other hand, at the median and upper quantiles we find a non-linear relationship, supporting the hypothesis of " U-inverted ". We need to highlight that the turning point is bigger at the upper quantile, where families have lower level of altruism. In general, the results indicate that the preferences of the parents are the primary determinant of child labor. Chapter 3: Child labor in urban Brazil: what is the role of the family structure? The aim of this chapter is to investigate the role of single parents on child labor in urban Brazil. We use data provided by Brazilian Demographic Census of 2010 and the models to determine the probability of working (Probit, IV-Probit and Bivariate Probit) and the Yun’s decomposition to capture the differences at the probability of child labor attributed to the difference in behavior between single-parent families, headed by the mother, and two-parent, headed by his father. The results show that boys, age 15 whose parents have low level of education are more likely to work. We also found evidences that children in single-parent homes are more likely to work when compared with children in two-parent households in the father’s responsibility, noting that the most vulnerable scenery for the child is to live in a single parent home with no widowed mother. And the difference in child labor between the two groups of families is mainly due to their unobserved behaviors.